2008
DOI: 10.2174/092986708784911515
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and Bioactivity of Flos Magnoliae, A Chinese Herb for Rhinitis and Sinusitis

Abstract: Flos Magnoliae (FM, Chinese name: Xin-yi) is one of the most commonly used Chinese medicinal herbs. It has a long history of clinical use for managing rhinitis, sinusitis and headache. More than 20 different FM species have been used clinically, which makes species identification and evaluation of pharmacological effects of individual chemical ingredients difficult. In this review, we have summarized the current knowledge on FM phytochemistry and its bioactivity activities. The bioactive compounds in FM includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 30 publications
0
24
0
1
Order By: Relevance
“…Pharmacological tests have revealed that Magnolia biondii Pamp possesses significant anti-inflammatory activities (Masayasu et al, 1985;Shen et al, 2008). Volatile oil in Magnolia biondii Pamp (VOMbP), is considered to be one important group of the pharmacologically active individuals against acute inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological tests have revealed that Magnolia biondii Pamp possesses significant anti-inflammatory activities (Masayasu et al, 1985;Shen et al, 2008). Volatile oil in Magnolia biondii Pamp (VOMbP), is considered to be one important group of the pharmacologically active individuals against acute inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…More than 80 reports have investigated the anti-inflammatory effect of Kampo medicines (reviewed in Refs. [24] and [25]). However, basic research and clinical studies for the treatment of oral diseases are much less [26][27][28][29][30], and little is known about the relative potency of Kampo medicines.…”
Section: Discussionmentioning
confidence: 98%
“…[1,2,3,4,5]. Magnolin, epimagnolin A, dimethyllirioresinol, eudesmin, and fargesin exhibit various biological activities, including anti-inflammatory activity [6,7,8,9,10], 5-lipoxygenase inhibitory activity [6], antimycobacterial activity [11], and the inhibition of tumor growth and cancer-catalyzed bone destruction [12]. Fargesin exhibits additional biological activities, including β1-adrenergic receptor antagonistic and cardioprotective effects [13], stimulation of basal glucose uptake and glucose transporter-4 translocation in muscle cells [14], treatment of dyslipidemia and hyperglycemia in high-fat diet-induced obese mice via activation of Akt and 5′-adenosine monophosphate-activated protein kinase in white adipose tissue [15], and antihypertensive effects in 2K1C hypertensive rats [16].…”
Section: Introductionmentioning
confidence: 99%